Case study 10 - Bahco treatment wetland for effluent final polishing (Argentina) - Maine, Maria Alejandra (2019)
Bahco metallurgical industry for toolmaking needed an effluentfinal stage treatment. A large land area was available in thefactory facilities and costs for maintance and operation ofwatewater treatment are limiting factors in Argentina. In addition,sewage from the factory also required a final treatment.A FWS wetland was constructed. This type of TW was selecteddue to the efficiency in metal removal and the low costs foroperation and maintenance. Although FWSs requires a largearea, this is not a problem in this case. Industrial wastewatercontaining metals and sewage from the factory are treatedtogether, both after a primary treatment (25 m3 d-1 of sewage +75 m3 d-1 of industrial wastewater). Sewage improves the abilityof macrophytes to take up heavy metals from wastewater.